Optimization of Expression Condition, Two Dimensional And Melting Point-Based Characterization of Recombinant Human Interferon Alpha-2a Fusion and Non Fusion Forms - Ningrum, Ratih Asmana; Wardhani, Widdya Kusuma; Wahyuni, Ike; Mustopa, Apon Zaenal (BRIN, 2018)
Recombinant Human Interferon Alpha-2a (rhIFNα-2a) is a therapeutic protein that used in hepatitis and cancer treatments. In our previous research, we developed higher molecular weight of the protein through human serum albumin fusion. The fusion and non fusion form of rhIFNα-2a were produced in Pichia pastoriswith 86 kDa and 19 kDa in size respectively. In previous research, protein yield was not reproducible due to unoptimized expression conditions. This reseach was aimed to optimize expression condition process and to characterize the fusion and non fusion forms of rhIFNα-2a. The parameters to observe in overproduction include nutrient (media and methanol concentration) and non nutrient (temperature andincubation period). Affinity and size exclusion cromatographicwere compared in protein purification. BCA assay was used to determine quantity of protein. Protein characterization was conducted using two-dimensional SDS PAGE and denaturation analyses. The optimal condition of expression was achieved using complex media with 1% of methanol for 3 day incubation period at 25°C. The protein yield was reproducible and higher comparing to previous research. Affinity chromatography resulted in higher purity of the proteins comparing to size exclusions. Characterization using two dimensional gel analysis revealed that isoelectric point of rhIFNα-2a is 6.5 for fusion form and 6.0 for non fusion form. The melting points of fusion protein were 56°C and 62°C whilst that of non fusion was 56°C.